Visual Acuity Outcomes in Patients Receiving Frequent Treatment of Neovascular Age-Related Macular Degeneration in Clinical Practice. (May 2021) - Moshfeghi, Andrew A.; Pitcher, John D.; Lucas, Genevieve; Boucher, Nick; Saroj, Namrata
Purpose: This work evaluates dosing frequency with intravitreal antivascular endothelial growth factor (anti-VEGF) agents over 2 years and visual acuity (VA) outcomes in neovascular age-related macular degeneration (nAMD). Methods: This retrospective analysis assesses electronic medical record data (Vestrum Health treatment and outcomes database) of newly diagnosed nAMD in patients who were initiated on intravitreal anti-VEGF treatment at US clinical sites. Eyes were divided into 2 injection frequency subcohorts (≤ 6 or > 6 injections/y); treatment frequency and change in mean VA (Early Treatment Diabetic Retinopathy Study letters) were evaluated. Results: Overall, 8127 of 213 824 eyes met inclusion criteria in year 1 and 4968 in year 2. During year 1, 77% of the eyes received more than 6 injections (n = 6287), the majority of which received injections at the same frequency during year 2. Mean VA gain from baseline at year 1 was lower in the ≤ 6 than > 6 injections/y subcohort (2.2 vs 6.5, P < .001). Decrease in mean VA from the end of year 1 to year 2 was significantly greater for eyes administered 6 or fewer injections in year 2 than those that received more frequent injections, irrespective of the frequency of injections in the first year. Conclusions: In routine clinical practice, most eyes with nAMD that completed at least 1 year of follow-up were treated with more than 6 injections of anti-VEGF agents during the first year of treatment, resulting in better VA gains than eyes treated less frequently during the same period.